Emporal and spatial variability of rainfall in modelling of stormwater outflows - Nowogoński, Ireneusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents issues related to modeling of the rainfall-runoff phenomenon. As factors influencing the simulation results, the velocity and direction of precipitation relative to the drainage basin were indicated. The possibility of underestimating the crosssections of rainwater channels as a result of overlapping rain wave directions and the dominant flow direction in the rainwater channel network was pointed out. The research results to date indicate a reduction in the symptoms of this phenomenon as the complexity of the channel network increases. The final verification was based on the actual catchment. Calculations were made using the Epa SWMM 5.1.013 software. The results are presented in a graphic form to illustrate the variability of stormwater outflow.
Keywords: rainfall; storm water; runoff; drainage; modeling; SWMM; opady; woda deszczowa; spływ; drenaż; modelowanie